Effect On Transfer Of Drainage System Flow Conditions Due To Construction Industry Settlement Of Shoes: (Case study: In Modong Village District of Tulangan On Sidoarjo Regency) - Gilang Yudha Akbar; Farida Hardaningrum (Journal of World Conference (JWC), 2020)
Industrial development in the village shoe Kepuhkemiri-Modong subdistrict of Sidoarjo regency Reinforcement require changing the flow pattern of the existing drainage channels affected by the construction. The shoe industry has a spacious area ±48.700 m2, so that the necessary planning measurable drainage system in order to move the existing flow patterns affected by construction. To calculate capacity analysis of new tertiary channel, channels in the industrial area, and the flow pattern in the area of ??the shoe industry. Data rainfall station includes four observation stations are Durungbedug, KETIMANG, Sidoarjo and Sumput and use rain observation period of 10 years. Channel overall flow of new tertiary and industrial areas in the channels piped to DAS 'Waterstand Channel' north side. Analysis of the design rainfall in this deign using the method of Log-Pearson III. The result of the rain discharge when the 5-year plan amounted to 121,369 m3 / sec, the channel carrying capacity of 2070m3, while the capacities of the channel plan with the calculations 2736,34 m3